miR-199a Overexpression Enhances the Potency of Human Induced-Pluripotent Stem-Cell–Derived Cardiomyocytes for Myocardial Repair - Bian, Weihua; Chen, Wangping; Nguyen, Thanh; Zhou, Yang; Zhang, Jianyi (Frontiers in Pharmacology, 2021)
Mammalian cardiomyocytes exit the cell cycle during the perinatal period, and although cardiomyocytes differentiated from human induced-pluripotent stem cells (hiPSC-CMs) are phenotypically immature, their intrinsic cell-cycle activity remains limited. Thus, neither endogenous cardiomyocytes nor the small number of transplanted hiPSC-CMs that are engrafted by infarcted hearts can remuscularize the myocardial scar. microRNAs are key regulators of cardiomyocyte proliferation, and when adeno-associated viruses coding for microRNA-199a (miR-199a) expression were injected directly into infarcted pig hearts, measures of cardiac function and fibrosis significantly improved, but the treatment was also associated with lethal arrhythmia. For the studies reported here, the same vector (AAV6-miR-199a) was transduced into hiPSC-CMs, and the cells were subsequently evaluated in a mouse model of myocardial infarction. AAV6-mediated miR-199a overexpression increased proliferation in both cultured and transplanted hiPSC-CMs, and measures of left ventricular ejection fraction, fractional shortening, and scar size were significantly better in mice treated with miR-199a–overexpressing hiPSC-CMs than with hiPSC-CMs that had been transduced with a control vector. Furthermore, although this investigation was not designed to characterize the safety of transplanted AAV6-miR-199a–transduced hiPSC-CMs, there was no evidence of sudden death. Collectively, these results support future investigations of miR-199a–overexpressing hiPSC-CMs in large animals.